Tracking of apolipoprotein B levels measured in childhood and adolescence: systematic review and meta-analysis - Stanesby Oliver; Zhou Zhen; Fonseca Ricardo; Kidokoro Tetsuhiro; Otahal Petr; Fraser Brooklyn J.; Wu Feitong; Juonala Markus; Viikari Jorma S. A.; Raitakari Olli T.; Tomkinson Grant R.; Magnussen Costan G. (Springer Nature, 2025)
To quantify the tracking of apolipoprotein B (apoB) levels from childhood and adolescence and compare the tracking of apoB with low-density lipoprotein (LDL) cholesterol, a systematic search of MEDLINE, Embase, Web of Science, and Google Scholar was performed in October 2023 (PROSPERO protocol: CRD42022298663). Cohort studies that measured tracking of apoB from childhood/adolescence (< 19 years) with a minimum follow-up of 1 year, using tracking estimates such as correlation coefficients or tracking coefficients, were eligible. Pooled correlations were estimated using random-effects meta-analysis. Risk of bias was assessed with a review-specific tool. Ten studies of eight unique cohorts involving 4677 participants met the inclusion criteria. Tracking of apoB was observed (pooled r = 0.63; 95% confidence interval [CI] = 0.53–0.71; I2 = 96%) with no significant sources of heterogeneity identified. Data from five cohorts with tracking data for both lipids showed the degree of tracking was similar for apoB (pooled r = 0.59; 95% CI = 0.55–0.63) and LDL cholesterol (pooled r = 0.58; 95% CI = 0.47–0.68). Study risk of bias was moderate, mostly due to attrition and insufficient reporting.
Conclusion: ApoB levels track strongly from childhood, but do not surpass LDL cholesterol in this regard. While there is strong evidence that apoB is more effective at predicting ASCVD risk than LDL cholesterol in adults, there is currently insufficient evidence to support its increased utility in pediatric settings. This also applies to tracking data, where more comprehensive data are required.